The use of mirrors to alleviate the detrimental effects of high stocking density on broiler chickens - Tamagi, H.M.; Idrus, Z.; Farjam, A.S.; Awad, E.A.; Hussein, A.N. (Verlag Eugen Ulmer, 2022)
A study was conducted to investigate whether providing mirrors as environmental enrichment to broiler chickens housed at two different stocking densities affects growth performance, behaviour and physiological stress responses. The experiment was conducted in a completely randomized design with a 2 × 2 factorial arrangement consisting of two stocking densities and two environmental enrichment regimens. A total of 208 day-old male broiler chicks were assigned to one of the four subgroups with eight replicates. Within each enrichment regimen [provision of mirrors (ME) or no-mirror (NM)], birds were raised at two stocking densities of low, 0.1000 m2/bird (5 birds/cage; LD) or high, 0.0625 m2/bird (8 birds/cage; HD) density from day 1 onward. On day 35, the HD-birds had a significantly lower feed intake and body weight than their LD counterparts. On day 34, the HD-broilers showed significantly more resting behaviour than those of the LD-group. Neither stocking density nor environmental enrichment had significant effects on other activities throughout the study. There were significant interactions between stocking density and environmental enrichment for serum levels of corticosterone (CORT) and ceruloplasmin (CPN) at day 35. Provision of mirrors resulted in similar CORT and CPN among the LD- and HD-chickens on day 35. However, the HD-NM birds had significantly higher CORT and CPN than the LD-NM group. Overall, the results suggest that the provision of mirrors has a negligible effect on growth performance, but can reduce the physiological stress response in broiler chickens with a higher stocking density.